AUTOMATIC SCREW JACK (International Journal of Engineering Sciences & Management Research, 2017)
Now a day with the increasing levels of technology, the efforts being put to produce any kind of work has been continuously decreasing. The efforts required in achieving the desired output can be effectively and economically decreased by the implementation of better designs. Power screws are used to convert rotary motion into translator motion. A screw jack is an example of a power screw in which a small force is applied in a horizontal plane is used to raise or lower a large load. The principle on which it works is similar to that of an inclined plane. The mechanical advantage of a screw jack is that the ratio of the load applied to the effort applied. The screw jack is operated by turning a lead screw. The height of the jack is adjusted by turning a lead screw and its adjustment can be done either manually or by integrating an electric motor. In this project, an electric motor will be integrated with the screw jack and the electricity needed for the operation is taken from the battery of the vehicle and thereby the mechanical advantage will be increased